1989
DOI: 10.1039/c39890001049
|View full text |Cite
|
Sign up to set email alerts
|

Selective carbonylation of propane in HF–SBF5: control of the activation step via the hydrocarbon/carbon monoxide ratio

Abstract: The selectivity of propane carbonylation in HF-SbF5 is found to depend on the propane/CO ratio, and is rationalized in terms of two competing activation processes for the alkane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The distribution of the observed reaction products, different from that formed from propane in the presence of solid Brønsted acid catalysts [11] and superacidic media [8,9,37], indicates that the activation of propane by SZ is performed primarily toward the secondary C-H bond of the alkane rather than its C-C bond. This can be realized by either the Lewis acid sites of SZ or by direct formylation by the formyl cation formed as equilibrated species from the formate.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The distribution of the observed reaction products, different from that formed from propane in the presence of solid Brønsted acid catalysts [11] and superacidic media [8,9,37], indicates that the activation of propane by SZ is performed primarily toward the secondary C-H bond of the alkane rather than its C-C bond. This can be realized by either the Lewis acid sites of SZ or by direct formylation by the formyl cation formed as equilibrated species from the formate.…”
Section: Discussionmentioning
confidence: 60%
“…Activation of propane in the presence of CO on H-ZSM-5 zeolite [11] proceeds in full analogy with the process in superacid media [8,9] via C-C bond cleavage to form methane and an ethyl cation. The ethyl cation abstracts a hydride ion from propane to form an isopropyl carbenium ion.…”
Section: Carbonylation Of Propane As Studied By 13 C Solid-state Nmrmentioning
confidence: 98%
See 1 more Smart Citation
“…573 K), no conversion of propane was reported at 473 K and below. [13] However, in analogy with the superacid-catalyzed protolytic activation of propane, [5,6] the Haag and Dessau mechanism (Scheme 1) would rationalize the formation of the same products.…”
Section: Resultsmentioning
confidence: 99%
“…Tertiary carbenium ions, which are produced by protolysis of CÀH bonds of branched alkanes in HF-SbF 5 , undergo skeletal isomerization and disproportionation before reacting with CO. 412 Two acylium (acyloxonium) ions, propanoyl cation (ethylcarboxonium ion, 112) and isobutyryl cation (isopropylcarboxonium ion, 113), were detected which, upon quenching (ethanol or NaHCO 3 /H 2 O), give the corresponding acids or esters [Eq. 408 It was also found that alkyl methyl ketones react with CO in the HF-SbF 5 superacid system to form oxocarboxylic acids after hydrolysis (Scheme 5.41).…”
Section: Carboxylationmentioning
confidence: 99%